The Implementation of Altruism Values Based on Hadith in Extracurricular Activities at Madrasah Aliyah - Bin Salman, Abdul Matin; Salma, Zakiati (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study aims to analyze the implementation of altruism values based on Hadith in extracurricular activities at Madrasah Aliyah Tiga Batur, Limapuluh Kota. This study employs a qualitative approach with a case study method, allowing the researcher to explore the application of altruism values in-depth within the specific context of the madrasah. Data were collected through observation, in-depth interviews, and document analysis, then analyzed using Hassan Hanafi's hermeneutic approach to understand the Hadith in its social and historical context and its relevance in the current educational situation. The results of the study show that extracurricular activities at Madrasah Aliyah Tiga Batur have successfully internalized altruism values through various specially designed programs, such as social activities and environmental care clubs. In conclusion, the integration of altruism values in these extracurricular activities is not only effective in shaping students' empathetic and caring character but can also serve as a model for other educational institutions that wish to instill Islamic values in the daily lives of their students.